Effects and potential pathways of goose astrovirus infection on gosling hepatic lipid metabolism - Chao Yin; Yun Shi; Haiqin Li; Zhihua Lu; Xiaona Gao; Guoliang Hu; Xiaoquan Guo (Frontiers in Microbiology)
IntroductionThe adverse effects of goose astrovirus (GoAstV) on avian growth and health have been widely reported previously, while the stress reactions and corresponding mechanism of gosling liver responding to GoAstV infection remain not entirely clear.MethodsOne-day-old goslings inoculated subcutaneously with 2 × 10−6 TCID50 of GoAstV were employed as an experimental model, and the potential effects and pathways of GoAstV infection on gosling liver functions were investigated by combining the morphological, biochemical and RNA sequencing (RNA-seq) techniques.ResultsStructural and functional impairments were found in gosling livers post the virus infection, as characterized by the histological alterations in liver index and morphology of hepatic cord and sinuses, as well as the abnormal expression patterns of the cellular antioxidant, inflammation and apoptosis-related genes. RNA sequencing analysis were performed to investigate the underlying mechanism. Results showed that the analysis of screened 1949 differentially expressed genes (DEGs) were mainly enriched in GO terms related to organic immune defense and substance metabolism, and their corresponding KEGG pathways represented by PPAR signaling pathway, intestinal immune network for IgA production, and fatty acid metabolism and degradation, suggesting that the functions of avian immunity and lipid metabolism were greatly changed after the GoAstV infection. Finally, the lipid deposition in gosling hepatocytes were further demonstrated by the subsequent Oil red O staining, biochemical detection of serum TG and HDL-C, and the gene expression analysis including PPARα, PPARγ, ACSBG2, ACSL5, CPT1A and PCK1.DiscussionThough limitations exist, the findings of this study are helpful to expand our understanding about the negative effects of GoAstV on goslings, and provide us with new clues for the salvaging of GoAstV-induced liver dysfunctions in poultry industry.